Search for T=1/2 states in H3 by elastic scattering of protons on deuterium - Daronian, D.; Faivre, J. C.; Garreta, D.; Goudergues, J.; Jungerman, J.; Krug, H.; Mayer, B.; Pages, A.; Papineau, A.; Testoni, J. E. (North Holland Publishing, 1967)
Fil: Daronian, D. Centre d'Etudes Nuclaires de Saclay; Francia